The five Ws taxonomy on customization of software as a service applications - Ali, Abdulrazzaq Qasem; Md Sultan, Abu Bakar; Abd Ghani, Abdul Azim; Zulzalil, Hazura (SandKRS, 2018)
Software as a Service has become a common model for various business applications. Increasingly, software application development companies have followed this model in delivering their software to their customers. SaaS delivery model is a multi-tenant model which reduces operational cost by increasing the resource sharing of one instance of application among multi customers (commonly named tenants). In this model, SaaS provider is not allowed to provide a copy of application code for each tenant, yet they have to permit each tenant to fulfill their different and varying requirements by enabling them to customize the application. This paper explores SaaS customization and the processes which make up the overall procedure. Accordingly, the Five Ws (who, when, what, where, and why) method is used to capture the core elements of SaaS customization, as well as how customization plays a role for the various SaaS stakeholders to introduce a taxonomy of SaaS customization. This taxonomy could provide guidance on SaaS customization.